The role of host microenvironment in the pathogenesis of multiple myeloma - Lwin, STS (2014)
Interactions between myeloma cells and cells of the bone marrow microenvironment promote tumour growth, survival and osteolytic bone disease. A greater understanding of the contributions of the host microenvironment to myeloma pathogenesis will ultimately identify new therapeutic approaches. An association between obesity and myeloma, or monoclonal gammopathy of undetermined significance (MGUS) has been shown previously. Matrix metalloproteinases (MMPs) are key regulators of tumour: host interactions due to their ability to alter the activity of multiple substrates. MMP7 has been implicated in breast and prostate cancer-mediated osteolysis. Interestingly, changes in serum MMP7 levels are found to correlate with changes in obesity, suggesting possible cross-talk between these mechanisms.